A New Brief Clinical Assessment of Lower Urinary Symptoms for Women and Men: The LURN Symptom Index – 10 (LURN SI-10) - Cella, David (J Urol, 2019)
PURPOSE: Lower urinary tract symptoms (LUTS) are common in men and women. The Lower Urinary Tract Dysfunction Research Network (LURN) sought to create a brief, clinically relevant tool to improve upon existing measurements of LUTS in both men and women. MATERIALS AND METHODS: Using a modified Delphi methodology during an expert consensus meeting, we reduced the LURN Comprehensive Assessment of Self-Reported Urinary Symptoms (CASUS) questionnaire to a very brief set of clinically-relevant items measuring LUTS. The sum score of these items was evaluated by comparing to the American Urological Association Symptom Index (AUA-SI), the Urinary Distress Inventory Short Form (UDI-6; in women only), and LUTS screening questions from CASUS, using Pearson correlations, regression analysis, and receiver operating characteristic (ROC) curves. RESULTS: The 10-item LURN-Symptom Index (LURN SI-10) assesses urinary frequency, nocturia, urgency, incontinence, bladder pain, voiding, and post-micturition symptoms (score range: 0–38). The correlation between the LURN SI-10 score and the AUA-SI was 0.77 in men and 0.70 in women. The UDI-6 and LURN SI-10 were highly correlated in women (r=0.76). The LURN SI-10 showed good accuracy in predicting both moderate and severe LUTS as defined by the AUA-SI (area under the ROC curve [AUC] range 0.82–0.90). Similar accuracy was shown in predicting different levels of symptom status using the UDI (AUC range 0.84–0.86). CONCLUSIONS: The LURN SI-10 correlates well with the AUA-SI and UDI-6. It includes items related to a broader spectrum of LUTS, particularly incontinence, bladder pain, and post-micturition symptoms, and applies to both men and women.